KAJIAN UPAYA PENGELOLAAN DAN PEMANTAUAN LINGKUNGAN PEMBANGUNAN RUMAH KHUSUS LANSIA KABUPATEN GORONTALO UTARA - Dr. Muhammad Ramdhan Olii, S.T.,M.Eng. (Universitas Gorontalo, 2022)
The construction of special homes for the elderly aims to provide proper facilities for the elderly so that they can rest and socialize with other elderly people in their old age, as well as reduce the housing backlog by 11.4 million people in Indonesia. Based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 4 of 2021, the construction of special houses is one type of business and/or activity that is required to have an environmental study based on its scale or magnitude. The purpose of this study is to identify the potential impact on the environment due to the business and/or activity of building a special house for the elderly in North Gorontalo Regency, both in the pre-construction stage, the construction stage to the operational stage. The method used in this study is a descriptive research method based on the Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. This study is a source of information on social, economic, and ecological problems that may arise in the future and methods of prevention and mitigation as a result of these development activities.Pembangunan rumah khusus lansia bertujuan untuk memberikan fasilitas yang layak bagi para lansia agar dapat beristirahat dan bersosialisasi dengan lansia lain di masa tua, serta mengurangi backlog perumahan sebesar 11,4 juta jiwa di Indonesia. Berdasarkan Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor 4 Tahun 2021, pembangunan rumah khusus merupakan salah satu jenis usaha dan/atau kegiatan yang wajib memiliki kajian lingkungan berdasarkan skala atau besarannya. Tujuan penelitian ini adalah mengidentifikasi potensi dampak terhadap lingkungan akibat usaha dan/atau kegiatan pembangunan rumah khusus lansia Kabupaten Gorontalo Utara baik tahap pra-konstruksi, tahap konstruksi hingga tahap operasional. Metode yang digunakan dalam kajian ini adalah metode penelitian deskriptif berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 22 Tahun 2021 tentang Penyelenggaraan Perlindungan dan Pengelolaan Lingkungan Hidup. Kajian ini menjadi sumber informasi permasalahan sosial, ekonomi, dan ekologi yang mungkin timbul dimasa yang akan datang dan metode pencegahan serta penanggulangan sebagai akibat adanya kegiatan pembangunan tersebut